2021
DOI: 10.1007/s41999-021-00475-7
|View full text |Cite
|
Sign up to set email alerts
|

Depression, antidepressants and fall risk: therapeutic dilemmas—a clinical review

Abstract: Purpose The aim of this clinical review was to summarize the existing knowledge on fall risk associated with antidepressant use in older adults, describe underlying mechanisms, and assist clinicians in decision-making with regard to (de-) prescribing antidepressants in older persons. Methodology We comprehensively examined the literature based on a literature search in Pubmed and Google Scholar, and identified additional relevant articles from reference li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 83 publications
2
40
0
2
Order By: Relevance
“…Similar to our study, patients with depression were reported to have increased odds for in-hospital fall related major injuries [38]. Depression and the use of antidepressant drug was found to increase falls risk [39,40]. Illicit drug use was reported to be associated with increased odds of injurious falls in patients living with HIV [41].…”
Section: Discussionsupporting
confidence: 83%
“…Similar to our study, patients with depression were reported to have increased odds for in-hospital fall related major injuries [38]. Depression and the use of antidepressant drug was found to increase falls risk [39,40]. Illicit drug use was reported to be associated with increased odds of injurious falls in patients living with HIV [41].…”
Section: Discussionsupporting
confidence: 83%
“…If left untreated, symptoms may persist for years. Both untreated depression and antidepressant use contribute to fall risk [ 107 , 128 ]. For details on fall risk and antidepressant use, we refer to the outcomes and recommendations of WG 2 (fall-risk increasing drugs, FRIDs).…”
Section: Assessmentmentioning
confidence: 99%
“…Also, excessive concern about falling contributes to increased fall risk in depressed older adults. It negatively influences gait and balance and thereby increases tendency to fall [ 128 ].…”
Section: Assessmentmentioning
confidence: 99%
“…3,4,21 This is due to the wide variety of adverse effects associated with antidepressants including but not limited to sedation, orthostatic hypotension, and anticholinergic effects. 37,38 Importantly, antidepressant use is reported by almost 13% of people in the United States illuminating that antidepressant use may be one of the most commonly encountered risk factors for postoperative falls by orthopaedic surgeons. 24 Jorgensen et al 13 in 2013 found that pharmacologically treated psychiatric disease was a major risk factor for falls after total hip arthroplasty.…”
Section: Discussionmentioning
confidence: 99%